NSO-1 biomarker ratios obtained by GC-QQQ-MS analyses in MRM and full scan mode - Katherine L French; Arne Leider; Christian Hallmann (PANGAEA, 2020)
This dataset provides biomarker ratios of the Norwegian Geochemical Standard North Sea Oil-1 (NSO-1) that was analyzed by gas chromatography triple quadrupole mass spectrometry (GC-QQQ-MS) on two instruments using independently developed analytical methods.